Preventive Detention And Constitutional Safeguards In Selected Third World Countries - Munir, Abu Bakar; Mohd Yassin, Siti Hajar bt (Journal of Malaysian and Comparative Law, 2019)
There comes a time during the life of almost every nation when situations arise which threaten its peace and security. At such a time the government may need to acquire certain additional powers to help it combat the danger.